Shear thickening fluid damper and its application to vibration mitigation of stay cable. (August 2020) - Lin, Kun; Zhou, Annan; Liu, Hongjun; Liu, Yi; Huang, Chenchao
Abstract: Stay cables are vital structure elements of cable-stayed bridges, which feature large span, high flexibility and low damping properties. The vibration control of stay cables is of very importance to ensure the serviceability and integrity of cable-stayed bridges. This paper concerns the design of a novel self-adaptive full-scale damper with shear thickening fluid (STFD) and its application to the mitigation of undesirable cable vibration. Dynamic experiments are performed to study the properties of the STFD under a series of sine wave at different frequencies but a constant amplitude. The output damping force of the STFD significantly increases as the velocity increases and a phenomenological model is proposed to fit the observed performance of the STFD. A general differential equation of the cable attached with a STFD is developed to solve the eigenvalue problem of the cable-STFD system by the finite difference method. This method also provides a tool for accurate determination of decay process and damping force. The results show that, for a cable-STFD system, the STFD produces a combined performance of friction damper and viscous damper. The features of either friction damper or viscous damper predominates at different stages of the decay process. The comparison also shows that, in general, the STFD is more effective on the mitigation of the stay cable vibration by comparing to the cable attached a viscous damper.